Prairie Christmas - Van Steenwyk, Elizabeth (Eerdmans Books for Young Readers, 2006)
On the Nebraska prairie in 1880, eleven-year-old Emma finds a way to celebrate the spirit of Christmas while her mother, a midwife, delivers a baby on Christmas Eve.